Massive tarsal coalition with extended tarsometatarsal coalition in a child: a case report - Yang, Lei; Yang, Xiaodong; Jiang, Jun; Tang, Xueyang (Frontiers in Pediatrics, 2024)
Tarsal coalition refers to a union of two or more tarsal bones, which mostly involves the calcaneonavicular and the talocalcaneal joints, but is rare in multiple unions or unions extended to the metatarsal bones. Nearly 50% of cases occur bilaterally and can be symmetrically or not. We described a rare case of symmetrically bilateral tarsal coalitions involving all the tarsal bones except for the medial cuneiform and extending to the fourth metatarsal bones in a 5-year-old male. This patient had no obvious symptoms and had not received any further intervention, only regular follow up. To our knowledge, this is the first report of this type involving the massive tarsal and one unique tarsometatarsal bilaterally.